2021
DOI: 10.1002/ecs2.3299
|View full text |Cite
|
Sign up to set email alerts
|

Estimating animal abundance and effort–precision relationship with camera trap distance sampling

Abstract: Effective monitoring methods are needed for assessing the state of biodiversity and detecting population trends. The popularity of camera trapping in wildlife surveys continues to increase as they are able to detect species in remote and difficult-to-access areas. As a result, several statistical estimators of the abundance of unmarked animal populations have been developed, but none have been widely tested. Even where the potential for accurate estimation has been demonstrated, whether these methods estimator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 50 publications
1
40
0
1
Order By: Relevance
“…We were, however, not able to identify the individuals or to obtain enough information on animal movements of the different species object to this study to analyze the data in a more robust way. We did not attempt the camera trap distance sampling method (CTDS; [58]) as with our reduced sample size in terms of locations of camera traps the coefficient of variation would have been too high [59]. Additionally, one of the main limitations in the use of CTDS can be the delay between the time the sensor is activated and the time the first image is recorded [58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We were, however, not able to identify the individuals or to obtain enough information on animal movements of the different species object to this study to analyze the data in a more robust way. We did not attempt the camera trap distance sampling method (CTDS; [58]) as with our reduced sample size in terms of locations of camera traps the coefficient of variation would have been too high [59]. Additionally, one of the main limitations in the use of CTDS can be the delay between the time the sensor is activated and the time the first image is recorded [58].…”
Section: Discussionmentioning
confidence: 99%
“…We did not attempt the camera trap distance sampling method (CTDS; [58]) as with our reduced sample size in terms of locations of camera traps the coefficient of variation would have been too high [59]. Additionally, one of the main limitations in the use of CTDS can be the delay between the time the sensor is activated and the time the first image is recorded [58]. Since we set the cameras to record at an automatic sensor level, we believe that this would have biased the estimates via CTDS as the trigger speed in automatic mode varies depending on the weather.…”
Section: Discussionmentioning
confidence: 99%
“…Distance sampling therefore requires accurate measurements of these distances. Camera trap data have also been successfully used as point transects (Bessone et al, 2020;Cappelle et al, 2019Cappelle et al, , 2020Howe et al, 2017), which requires the recording of distances at which recorded animals pass in front of the camera. Numbers of replicates (points) and detections (distance measurements) required for robust estimation are comparable to those required on line and point transects by human observers (Bessone et al, 2020;Cappelle et al, 2020).…”
Section: Distance Samplingmentioning
confidence: 99%
“…Bessone et al (2020) obtained an average CV of 0.37 in spite of sampling 750 locations. In this respect,Cappelle et al (2021) concluded that a wide variety of survey designs can be applied to achieve CV between 0.10 and 0.20 with CT-DS, for instance, with at least 100 sampling days at as few 50 camera trap placements. Future field studies are needed to evaluate the improvement in precision regarding the number of sampled locations.…”
mentioning
confidence: 99%